Longitudinal assessment of hippocampus structure in children with type 1 diabetes. Issue 6 (21st May 2018) - Foland‐Ross, Lara C; Reiss, Allan L; Mazaika, Paul K; Mauras, Nelly; Weinzimer, Stuart A; Aye, Tandy; Tansey, Michael J; White, Neil H
Abstract : The extant literature finds that children with type 1 diabetes mellitus (T1D) experience mild cognitive alterations compared to healthy age‐matched controls. The neural basis of these cognitive differences is unclear but may relate in part to the effects of dysglycemia on the developing brain. We investigated longitudinal changes in hippocampus volume in young children with early‐onset T1D. Structural magnetic resonance imaging data were acquired from 142 children with T1D and 65 age‐matched control subjects (4‐10 years of age at study entry) at 2 time points, 18 months apart. The effects of diabetes and glycemic exposure on hippocampal volume and growth were examined. Results indicated that although longitudinal hippocampus growth did not differ between children with T1D and healthy control children, slower growth of the hippocampus was associated with both increased exposure to hyperglycemia (interval HbA1c) and greater glycemic variability (MAGE) in T1D. These observations indicate that the current practice of tolerating some hyperglycemia to minimize the risk of hypoglycemia in young children with T1D may not be optimal for the developing brain. Efforts that continue to assess the factors influencing neural and cognitive development in children with T1D will be critical in minimizing the deleterious effects of diabetes.